2017
DOI: 10.1002/osp4.114
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and prospective associations between physical activity, body mass index and waist circumference in children and adolescents

Abstract: SummaryObjectiveTo study the cross‐sectional and prospective associations between physical activity (PA) of different intensities, body mass index (BMI) and waist circumference (WC) in children and adolescents using isotemporal substitution modelling.MethodsPhysical activity (accelerometry), BMI and WC were assessed in 6‐ (n = 970), 9‐ (n = 2,423) and 15‐year‐olds (n = 1,544) in 2005/2006 and 2011/2012. Participants aged 9 years in 2005/2006 were followed prospectively to 2011/12 (age 15). Associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
(62 reference statements)
2
25
0
2
Order By: Relevance
“…Another finding was that average daily measured MVPA decreased with children's age (Figure 2b). This result is consistent with previous studies of Norwegian children [26,27], as well as other research carried out worldwide [28][29][30]. This pattern can probably be explained with increases in mass of older children leading to increases in body inertia.…”
Section: Discussionsupporting
confidence: 93%
“…Another finding was that average daily measured MVPA decreased with children's age (Figure 2b). This result is consistent with previous studies of Norwegian children [26,27], as well as other research carried out worldwide [28][29][30]. This pattern can probably be explained with increases in mass of older children leading to increases in body inertia.…”
Section: Discussionsupporting
confidence: 93%
“…[ 17 , 39 ] Because PA in daily life is mostly LPA, it is relatively easy to replace SB with 30 or 60 minutes of LPA; however, it is too ambitious and difficult to replace SB with 60 or even 30 minutes of MVPA . [ 21 ] Another study suggested that the bout length should be at least 10 minutes, as this was the lowest cumulative time of MVPA required to receive health benefits. [ 40 ] However, recent studies have shown that participation in MVPA, regardless of duration, can reduce all-cause mortality, cancer mortality, and the risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al [ 17 ] and Jones et al [ 19 ] used a 30-minute substitution time to investigate the effect on CRF of replacing SB with PA of different intensities; however, the 30-minute substitution time was clearly too ambitious and difficult to achieve. [ 17 , 21 ] Collings et al [ 18 ] chose an alternative length of 10 minutes, which may accumulate less time for MVPA than the recommended amount of 60 minutes. Further research is needed on how to determine the appropriate substitution time duration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also showed inverse association between replacing sedentary time with VPA and childhood obesity. K. Dalene et al reported that replacing 10 min/day sedentary time with VPA and MPA were cross-sectionally associated with lower BMI and WC both in children and adolescents [ 24 ]. Other cross-sectional studies indicated that replacing 10 min/day of sedentary time with VPA was associated with fat mass index among children aged 6–11 years [ 25 ], and substituting 5 min/day sedentary time with VPA was associated with adiposity markers among preschool children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%